Isu Lingkungan Hidup Global: Tantangan Kebijakan Luar Negeri dan Negosiasi Multilateral - Isnaeni, Nurul; Wardoyo, Broto (Global: Jurnal Politik Internasional, 2007)
- Nowadays environmental issue has been a main topic in international affairs. Hundreds of international environmenta! agreement has been born in the last three decades, which reflects state-actors' choice through its foreign-policy that is to cooperate in the complex dynamics of environmental issue. International cooperation process itself actually is a complex political bargaining, as it tries to harmonize varied interests. Therefore, diplomacy has been an important policy instrument in order to bridge those varied interests. The question is how to define diplomacy practice in multilateral level that involves a complex political process along with multi actors, characters, and interests? This article boards from preposition that a representative diplomats, instead of defines the essence of environmental issue in the foreign-policy context as global politic dynamics, must also have the understanding about the essence of diplomacy and the court's procedures in multilateral conference in order to focus to its goals.